2018
DOI: 10.2465/jmps.170721
|View full text |Cite
|
Sign up to set email alerts
|

Geochemical, structural and morphological characterization of vein graphite deposits of Sri Lanka: Witness to carbon rich fluid activity

Abstract: is endowed with high purity vein graphite deposits with extensive mineralization in the tectonically weakened zones of the basement high-grade rocks. Distinctly different crystal shapes of graphite are found even within a single vein and it is controversial in interpreting prevailed fluid activities and crystallization process to form such a variation. Therefore, this study was carried out to interpret the origin of vein graphite using geochemistry, crystal-morphology, and structure of the crystals. Sampling w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…For the present study, Needle Platy Graphite (NPG), which usually possesses the highest purity among the four structural varieties of Sri Lankan vein graphite (Hewathilake et al, 2018) was collected from a deep underground mine. Figure 2 shows a sample of the Needle Platy Graphite variety of Sri Lankan Vein Graphite.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the present study, Needle Platy Graphite (NPG), which usually possesses the highest purity among the four structural varieties of Sri Lankan vein graphite (Hewathilake et al, 2018) was collected from a deep underground mine. Figure 2 shows a sample of the Needle Platy Graphite variety of Sri Lankan Vein Graphite.…”
Section: Methodsmentioning
confidence: 99%
“…Figure 1 depicts the schematic diagram showing the crystalline structure of graphite. Pristine graphite has an interlayer spacing of 3.354 Å (Hewathilake et al, 2018). Under ambient conditions, Lithium ions are gradually inserted between single graphite layers, and a maximum of one lithium per six carbons (LiC 6 ) is expected to be intercalated, in the Van der Waals gaps above and below a carbon hexagon (Figure 1) (Deng, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…These properties of graphite make it an attractive material for many technological applications 1 , 2 . Naturally occurring graphite has a wide range of purities depending on its geological occurrence 3 – 5 .…”
Section: Introductionmentioning
confidence: 99%
“…Although the carbon content of vein graphite varieties is considered to be high up to about 90–99.8%, their natural purity is often in the lower-end of this range due to the presence of gangue minerals which are naturally associated with the graphite veins 5 , 13 . Furthermore, the purity of natural vein graphite varies from place to place in the same deposit.…”
Section: Introductionmentioning
confidence: 99%
“…(1) arrested charnockitization (e.g., Hansen et al, 1987;Hiroi et al, 1990;Yoshida and Santosh, 1994;Kehelpannala, 1999;Perchuk et al, 2000, and references therein), (2) high purity vein graphite deposits (e.g., Erdosh, 1970;Hapuarachchi, 1977;Dissanayake, 1986;Hewathilake et al, 2018 ;Touret et al, 2019, and references therein), (3) occurrence of ultrahigh-temperature (UHT) mineral assemblages such as sapphirine + quartz and orthopyroxene + sillimanite + quartz (e.g., Osanai, 1989;Hiroi et al, 1994, Kriegsman andSchumacher, 1999;Sajeev and Osanai, 2004;Dharmapriya et al, 2015;Osanai et al, 2016a, and references therein), and so on. I have carried out petrological study of them for more than thirty years and found such interesting features as follows; (1) occurrences of relict prograde kyanite and staurolite with or without sapphirine and spinel in khondalite and UHT pelitic granulites as well as retrograde andalusite in various rocks (e.g., Hiroi et al,1987Hiroi et al, , 1990Hiroi et al, , 1994Ogo et al, 1992), (2) occurrence of garnet preserving compositional growth zoning of major and trace elements in granulite-facies rocks (Hiroi et al, 1995(Hiroi et al, , 1997a, (3) occurrence of Fe-rich kornerupine in pegmatite (Grew et al, 1995), (4) partial replacement of cordierite by andalusite + carbonate + quartz aggregates and ilmenite by rutile + siderite as the result of local infiltration of CO 2 (Hiroi et al, 1990;Ellis and Hiroi, 1997), (5) replacement of sillimanite and garnet by spinel + feldspar ± corundum intergrowths in some deformed khondalites (graphitic garnet-sillimanite gneiss) (Hiroi et al, 1997b), (6) metasomatic cordierite formation after plagioclase (Hiroi et al, unpublished data), and so on.…”
Section: Introductionmentioning
confidence: 99%